Detection of Bartonella quintana by Direct Immunofluorescence Examination of Blood Smears of a Patient with Acute Trench Fever - Foucault, C. (American Society for Microbiology, 2004)
We report a case of Bartonella quintana acute symptomatic infection in a homeless man, presenting as a typical trench fever. B. quintana has been retrieved in erythrocytes in large clusters and in erythroblasts. Direct immunofluorescence of blood smears allows a rapid diagnosis.